Innovation of Cooling System Learning Media Android-Based Air Using Smart Apps Creator for Vocational High School Students - Andri Setiyawan; Rizal Alvindo; Arief Kurniawan; Lena Citra Manggalasari (Journal of Vocational Education Studies, 2023)
This study aims to develop Android-based cooling system maintenance learning media using Smart Apps Creator, determine the feasibility and effectiveness of the media, and determine students' responses after using the learning media that has been developed. This research is a type of research and development developed using the ADDIE development model. The resulting product is an Android application made using Smart Apps Creator. Product trials were carried out using a one-group pretest-posttest design, while the instruments used were questionnaires and test instruments. The results of this study are that this learning media gets "Very Feasible" results based on the assessment results from material experts and media experts, with an average percentage of 93.13% feasibility from material experts and 87.73% from media experts. Learning media is effective for use in the learning process. This is based on the t-test results, which get a value of t-score. 11.65, or it can be concluded that there is a significant increase in learning outcomes after using learning media. Students also responded excellently to using learning media, with a percentage of 86.71%.